Application of Nanomaterials to Enhance Polymerase Chain Reaction - Zhu Yang; Bei Shen; Lihuan Yue; Yuqing Miao; Yihong Hu; Ruizhuo Ouyang (Molecules, 2022)
Polymerase Chain Reaction (PCR) is one of the most common technologies used to produce millions of copies of targeted nucleic acid in vitro and has become an indispensable technique in molecular biology. However, it suffers from low efficiency and specificity problems, false positive results, and so on. Although many conditions can be optimized to increase PCR yield, such as the magnesium ion concentration, the DNA polymerases, the number of cycles, and so on, they are not all-purpose and the optimization can be case dependent. Nano-sized materials offer a possible solution to improve both the quality and productivity of PCR. In the last two decades, nanoparticles (NPs) have attracted significant attention and gradually penetrated the field of life sciences because of their unique chemical and physical properties, such as their large surface area and small size effect, which have greatly promoted developments in life science and technology. Additionally, PCR technology assisted by NPs (NanoPCR) such as gold NPs (Au NPs), quantum dots (QDs), and carbon nanotubes (CNTs), etc., have been developed to significantly improve the specificity, efficiency, and sensitivity of PCR and to accelerate the PCR reaction process. This review discusses the roles of different types of NPs used to enhance PCR and summarizes their possible mechanisms.